How vital is the voice? The use of vocal activities in group music therapy with institutionalised individuals with Cerebral Palsy in providing opportunities for self-expression and social interaction - Pavlicevic, M. (University of Pretoria, 2013)
Dissertation (MMus)--University of Pretoria, 2012.